Effect ofcinnoline sulphonamide derivatives in canine mammary and venereal tumours - SAXENA, V; MAITI, S K; KUMAR, N; SHARMA, A K (The Indian Journal of Animal Sciences, 2011)
The chemotherapeutic agent, cinnoline sulphonamide derivative was administered @ 500 nlg orally in each spontaneously occur canine mammary tumour and transmissible venereal tumour cases in different breeds of dogs. The drug was found very much effective in 66% mammary tumour and 50% venereal tumour cases. The drug was effective in small size (2-3 cm) and recently developed tumours. The side effect was temporary and minimal. Â